2020
DOI: 10.1007/s11005-020-01333-6
|View full text |Cite
|
Sign up to set email alerts
|

Bulk-boundary asymptotic equivalence of two strict deformation quantizations

Abstract: The existence of a strict deformation quantization of $$X_k=S(M_k({\mathbb {C}}))$$ X k = S ( M k ( C ) ) , the state space of the $$k\times k$$ k × k matrices $$M_k({\mathbb {C}})$$ M k ( C ) which is canonically a compact Poisson manifold (with stratified boundary), has recently been proved by both authors and Landsman (Rev Math Phys 32:2050031, 2020. 10.1142/S0129055X20500312). In fact, since increasing tensor powers of the $$k\times k$$ k × k matrices $$M_k({\mathbb {C}})$$ M k (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…N now implies that the algebraic vector state ω (0) 1/N is strictly invariant under Z 2 : no SSB occurs for any finite N . In a similar fashion as above (see for example [35] and references therein) one can prove that the algebraic vector state ω…”
Section: Mean-field Theoriesmentioning
confidence: 70%
“…N now implies that the algebraic vector state ω (0) 1/N is strictly invariant under Z 2 : no SSB occurs for any finite N . In a similar fashion as above (see for example [35] and references therein) one can prove that the algebraic vector state ω…”
Section: Mean-field Theoriesmentioning
confidence: 70%
“…In what follows we consider mean field quantum spin systems whose Hamiltonians H 1/N are restricted to this subspace, since quantum spin systems arising in that way are tipically of the form Q 1/N (h N ) for some (N-dependent) real polynomial function h N on M = S 2 given by (1.26) and Q 1/N given by (1.20) -(1.21) (see e.g. [19,Theorem 3.1] for an example). Such spin systems are widely studied in (condensed matter) physics, but also in mathematical physics they form an important field of research.…”
Section: Mean-field Theories and Symbolmentioning
confidence: 99%
“…Let us first stress that the limit N → ∞ can be taken in two entirely different ways, which depends on the class of observables one considers, namely either quasi-local observables or macroscopic observables. The former are the ones traditionally studied for quantum spin systems, but the latter relate these systems to strict deformation quantization, since macroscopic observables are precisely defined by (quasi-) symmetric sequences which form the continuous cross sections of a continuous bundle of C * -algebras [16,19,15]. In [19,Theorem 2.3] it has been shown that the quantization maps (1.20) -(1.21) define quasi-symmetric sequences, and hence macroscopic observables.…”
Section: Classical Limitmentioning
confidence: 99%
“…However, different approaches were used and no limit of a sequence of eigenvectors was taken. More recent studies [14,17,30,25] have shown a well-established relation between the classical limit of a sequence of eigenvectors associated to mean-field quantum spin system Hamiltonians and spontaneous symmetry breaking. In these relatively simple systems, where the Hamiltonian is always a bounded operator, the symmetry group is typically finite.…”
mentioning
confidence: 99%